2019
DOI: 10.1111/jgs.16159
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Osteoarthritis and Social Isolation: Data From the EPOSA Study

Abstract: OBJECTIVE To determine whether there is an association between osteoarthritis (OA) and incident social isolation using data from the European Project on OSteoArthritis (EPOSA) study. DESIGN Prospective, observational study with 12 to 18 months of follow‐up. SETTING Community dwelling. PARTICIPANTS Older people living in six European countries. MEASUREMENTS Social isolation was assessed using the Lubben Social Network Scale and the Maastricht Social Participation Profile. Clinical OA of the hip, knee, and hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…Los pacientes con artrosis pueden tener dificultades para llevar a cabo actividades de la vida diaria como ir al baño, caminar o vestirse 8 . Estas limitaciones se han relacionado en varios países, entre ellos España, con situaciones de aislamiento social 9 . En conjunto, vivir con dolor crónico, fatiga, restricciones de actividades o aislamiento social contribuye a la depresión en la artrosis 10 y tiene relación con una menor calidad de vida de los pacientes 11 .…”
Section: Introductionunclassified
“…Los pacientes con artrosis pueden tener dificultades para llevar a cabo actividades de la vida diaria como ir al baño, caminar o vestirse 8 . Estas limitaciones se han relacionado en varios países, entre ellos España, con situaciones de aislamiento social 9 . En conjunto, vivir con dolor crónico, fatiga, restricciones de actividades o aislamiento social contribuye a la depresión en la artrosis 10 y tiene relación con una menor calidad de vida de los pacientes 11 .…”
Section: Introductionunclassified
“…Social participation is a frequently overlooked variable, yet it has previously been associated with higher mortality rates [ 36 ]. Previously, less social participation has been associated in patients with OA, and it has been suggested that it could be caused by poorer physical ability [ 37 ]. In this regard, it has been suggested that depression can be understood as a continuum of affective disorders developed by the influence of biopsychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…[21] also found a signi cant association between pain severity and impact thereof on both BADLs and IADLs in older adults with OA among other disorders. The European Project on OSteoArthritis (EPOSA study), aimed at investigating the consequences of the most common forms of OA in older adults using data from six European countries, including Spain [37], found that clinical OA, present in one or two sites (hip and knee), or in two or three sites (hip, knee, and hand), increased the risk of social isolation, cognitive impairment and worse walking and physical activity [38,39]. These ndings are consistent with our analysis, particularly in the moderate to severe pain group, although the EPOSA study did not analyze whether the presence of pain interferes with activities of daily living [40].…”
Section: Discussionmentioning
confidence: 99%